A Tripartite, Hierarchical Sigma Factor Cascade Promotes Hormogonium Development in the Filamentous Cyanobacterium Nostoc punctiforme - Alfonso Gonzalez (American Society for Microbiology, 2019)
ABSTRACT Cyanobacteria are prokaryotes capable of oxygenic photosynthesis, and frequently, nitrogen fixation as well. As a result, they contribute substantially to global primary production and nitrogen cycles. Furthermore, the multicellular filamentous cyanobacteria in taxonomic subsections IV and V are developmentally complex, exhibiting an array of differentiated cell types and filaments, including motile hormogonia, making them valuable model organisms for studying development. To investigate the role of sigma factors in the gene regulatory network (GRN) controlling hormogonium development, a combination of genetic, immunological, and time-resolved transcriptomic analyses were conducted in the model filamentous cyanobacterium Nostoc punctiforme, which, unlike other common model cyanobacteria, retains the developmental complexity of field isolates. The results support a model where the hormogonium GRN is driven by a hierarchal sigma factor cascade, with sigJ activating the expression of both sigC and sigF, as well as a substantial portion of additional hormogonium-specific genes, including those driving changes to cellular architecture. In turn, sigC regulates smaller subsets of genes for several processes, plays a dominant role in promoting reductive cell division, and may also both positively and negatively regulate sigJ to reinforce the developmental program and coordinate the timing of gene expression, respectively. In contrast, the sigF regulon is extremely limited. Among genes with characterized roles in hormogonium development, only pilA shows stringent sigF dependence. For sigJ-dependent genes, a putative consensus promoter was also identified, consisting primarily of a highly conserved extended −10 region, here designated a J-Box, which is widely distributed among diverse members of the cyanobacterial lineage. IMPORTANCE Cyanobacteria are integral to global carbon and nitrogen cycles, and their metabolic capacity coupled with their ease of genetic manipulation make them attractive platforms for applications such as biomaterial and biofertilizer production. Achieving these goals will likely require a detailed understanding and precise rewiring of these organisms’ GRNs. The complex phenotypic plasticity of filamentous cyanobacteria has also made them valuable models of prokaryotic development. However, current research has been limited by focusing primarily on a handful of model strains which fail to reflect the phenotypes of field counterparts, potentially limiting biotechnological advances and a more comprehensive understanding of developmental complexity. Here, using Nostoc punctiforme, a model filamentous cyanobacterium that retains the developmental range of wild isolates, we define previously unknown definitive roles for a trio of sigma factors during hormogonium development. These findings substantially advance our understanding of cyanobacterial development and gene regulation and could be leveraged for future applications.